Autoimmune encephalitis update. Issue 6 (16th March 2014) - Dalmau, Josep; Rosenfeld, Myrna R.
Abstract: Cancer-associated immune-mediated disorders of the central nervous system are a heterogeneous group. These disorders include the classic paraneoplastic neurologic disorders and the more recently described autoimmune encephalitis associated with antibodies to neuronal cell-surface or synaptic receptors that occur with and without a cancer association. Autoimmune encephalitis is increasingly recognized as the cause of a variety of neuropsychiatric syndromes that can be severe and prolonged. In contrast to the classic paraneoplastic disorders that are poorly responsive to tumor treatment and immunotherapy, autoimmune encephalitis often responds to these treatments, and patients can have full or marked recoveries. As early treatment speeds recovery, reduces disability, and decreases relapses that can occur in about 20% of cases, it is important that the immune pathogenesis of these disorders is recognized.